Asphalt and Concentrated Rubber Latex Mixing Machine for Highway Engineering Laboratory Testing - Aueatchaisai, Somsak; Punlor, Ankana (Frontiers in Engineering Innovation Research, 2020)
The objective of this research is to design and build the mixing machine for asphalt emulsion and concentrated rubber latex which can be used in the laboratory efficiently and safely. Firstly, the conceptual design of 3 types of mixing machine was created, to compare and find out the most suitable mixer construction type. After that, the mixing machine is built. The main components of the mixing machine are a mixer, material tank, stirrer, and support. After that, the most suitable mixing condition has to be found by using the laboratory testing results from Saybolt Furol viscosity, ductility, and penetration. It is found that 218 rpm mixing speed by using the hook stirrer and 7 minutes mixing time was the most suitable mixing condition because the mixture had a Saybolt Furol viscosity = 20.54 seconds, the ductility = 150 cm and the depth of penetration = 55.92 units which met the standard specification of the Department of Highway (DH-SP.405/2538). Moreover, manual mixing was also conducted. The results were then compared with the results of the mixing machine. It is found that the product from the mixing machine was stronger than from the manual mixing. From the overall results, it can be concluded that the mixing machine has good efficiency, because the mixing machine can decrease mixing time about 41% in comparison with manual mixing, reduce also material using and make working more comfortable and safe.